2022
DOI: 10.1111/ecc.13669
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychological distress among cancer patients in Southeast Asian countries: A systematic review

Abstract: Psychological distress (including depression and anxiety) is common in the first years of cancer diagnosis but can differ by country and region. The aim of the present paper was to review the prevalence of psychological distress among cancer patients in the Southeast Asia (SEA) region. A systematic literature search was carried out using several databases (i.e., PubMed, PsychARTICLES, Embase, CINAHI, Web of Sciences, Plus, Scopus, and AHMED). Papers originally published in English language were taken into cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 98 publications
0
14
2
3
Order By: Relevance
“…Research focusing on psychosocial needs has revealed regional and cultural variations in prevalence of anxiety, depression, and psychologic and informational needs across the region. 17 , 18 Studies of financial toxicity, a subjective burden of the cost of cancer and its treatment, including a systematic review and meta-analysis and an eight-country cohort study showed rates of financial toxicity as high as 83% and a 31% incidence of financial catastrophe. 19 , 20 There were also significant gaps in evidence, with no studies on needs of cancer survivors from the Pacific Islands and Territories.…”
Section: Symptom Burden and Supportive Care Needsmentioning
confidence: 99%
“…Research focusing on psychosocial needs has revealed regional and cultural variations in prevalence of anxiety, depression, and psychologic and informational needs across the region. 17 , 18 Studies of financial toxicity, a subjective burden of the cost of cancer and its treatment, including a systematic review and meta-analysis and an eight-country cohort study showed rates of financial toxicity as high as 83% and a 31% incidence of financial catastrophe. 19 , 20 There were also significant gaps in evidence, with no studies on needs of cancer survivors from the Pacific Islands and Territories.…”
Section: Symptom Burden and Supportive Care Needsmentioning
confidence: 99%
“… 30 In cancer patients, prevalence rates for PTSD, depression, and anxiety vary on the type of malignancy and methodology of follow-up, but they are similar to those reported in the ICU literature. 3 , [31] , [32] , [33] , [34] One-third of non-intubated patients in our study required non-invasive ventilation that may have been potentially distressing for them. Specifically, non-invasive ventilation can induce a psychological stress response, fear of dying, pain, and suffering; 35 in part caused by mask discomfort, feelings of claustrophobia, and impaired awareness may contribute to psychological distress.…”
Section: Discussionmentioning
confidence: 93%
“…[29,30] In Korea, where cancer is the leading cause of death, depression and anxiety are common among breast cancer patients and survivors, but often underdiagnosed and undertreated. [31] The Korean health system provides universal coverage for cancer treatment, but the access to and quality of mental health care and support systems for health and social welfare are still inadequate. [32,33] Our study of the Korean cohort further extends evidence on the long-term mortality impact of postbreast cancer diagnosis depression among 5-year cancer survivors, highlighting the need for screening and treating depression in breast cancer patients, especially in Asian populations where depression may be overlooked and undertreated.…”
Section: Discussionmentioning
confidence: 99%